GE_GERICHTE P/5366/2018 vom 23. Oktober 2018 - GE Cour de justice (2018)
DISPOSITIONS PÉNALES DE LA LETR ; RUPTURE DE BAN ; NE BIS IN IDEM ; INDEMNITÉ POUR DÉTENTION | LEtr.119.al1; CP.41; CP.42; CP.47; CP.49; CP.51; CP.291; CPP.135; CPP.428.al1; CPP.428.al3